Students’ Ability in Constructing Simple Present Sentence at SMP Negeri 4 Lage - Charles Setiawan Toedje (Sintuwu Maroso Journal of English Teaching, 2020)
The objective of the research is to find out the students’ achievement in constructing simple present sentence at the second grade of SMP Negeri 4 Lage. The method of the research is descriptive qualitative method. The role of the researcher is fully observer. The data are collected by giving the test. The technique of data analysis is used the following steps: correcting the students answer sheet, scoring the students answer, determining the level of students score. The result of the research is 1 student (5,26%) is good level, 2 students (10,52%) are less level and 16 students (84,2%) are poor level. None student is Excellent, and fair level. It can be concluded that the students’ achievement in constructing simple present tense in to the second grade at SMP Negeri 4 lage is poor level.